Minimum pavement lift thickness for Superpave mixtures - Paye, Barry; Bahia, Hussain (Wisconsin Highway Research Program, 2001)
The purpose of this study was to look at the effect of lift thickness as it relates to the density of Superpave Hot Mix Asphalts. The study consisted of two phases: (1) a laboratory study and (2) a field study. In the laboratory study, five different sample sizes ranging from 1,500 gm to 6,000 gm were compacted in the Superpave Gyratory Compactor from eleven different mixes. The specimens were analyzed for air voids, compactive resistance measured by the Gyratory Load Plate Assembly and reported as Construction Energy Index (CEI) and Construction Friction Index (CFI), and extracted gradation results. It was found that sample sizes smaller than 3,000 gm had significantly higher air voids, and the samples larger than 3,000 gm had about the same amount of air voids as the 3,000-gm samples. CEI and CFI results also demonstrated the same information as the air voids did, with smaller samples providing more compactive resistance. Extraction results showed no significant change in gradation due to the compaction process across all sample sizes. In the field study, four different projects were tested. Each project consisted of varying the lift thickness to see the effect it had on the density achieved, with lifts as thin as 1.25 in. tested. Mixes from granite, limestone and gravel sources were tested, with projects ranging from interstate highways to county trunk roads. The overall trend seen was that thickness had no effect on the density achieved, and that the thicker layers needed more roller passes to achieve the same density as the thinner ones. The recommendations from this study include looking at different mixtures and sources from those tested to check for similar results. It is further recommended that the lack of correlation between the lab and field be studied.
159 p.
Keywords: Recommendations; Aggregate gradation; Gyratory testing machines; Hot mix paving mixtures; Field studies; Limestone; Granite; Superpave; Density; Air voids